(untitled) (Journal of the College of Education for Women, 2018)
kindergarten teacher is one of the fundamental pillars upon which the kindergarten environment so that exposure to a number of problems that could affect its functioning in addition to any deficiencies in this environment leads to deprive a child of some activities and acquisition of concepts so the researcher studying the problems of working in kindergartens from the perspective of the parameters, so the researcher based measuring instrument for labour problems of (30) search sample was paragraph (50) parameter that was chosen at random and have been extracted Sincerity and strength tool researcher used statistical methods and discriminatory (Pearson correlation coefficient, t-test for independent samples, one sample t-test , one way anova, the weighted percentage weight) depending on what the researcher has developed the following objective; know what the business problems from the standpoint of kindergarten teachers by verifying the following hypothesis: statistical function differences exist between the arithmetic problems of work from the perspective of the parameters on the measuring instrument and Center this speculation when the level indication (0, 5) statistical function differences exist between average global problems from the standpoint of parameters and variable service when the level indication (0, 05).